The use of information on agrarian structure for strategy development in Spatial Planning: An account of the methods and results of case-studies from the area of planning and support strategies for nature conservation goals - Haaren, Christina von; Hein, Angela; Makala, Michael (Raumforschung und Raumordnung | Spatial Research and Planning, 1999)
Information on agrarian structure can make a valuable contribution to supplementing the strategies embodied in sectoral plans. Benefits can accrue for the process of selecting priorities for action and deciding on what locations are to be prioritised, for the preparation of plans, and equally for decisions on the approach to the implementation of planning measures. In two research projects a method has been developed which allows information on potential and availability for implementation — as well as on the scope for synergy effects between agriculture and nature conservation — to be integrated within strategies for greenfield protection at federal state level.